Characteristics of Fly Ash and Bottom Ash from Incinerators at Landfill Sites - Azhra Amanda, Tiffany; Chaerul, Mochammad; Sukandar, Sukandar (Universitas Andalas, 2025)
Waste management in Indonesia, especially in big cities, faces a big challenge as the volume of waste continues to increase every year. One of the technologies used to address this problem is incineration, which is the process of burning waste to reduce its volume and generate energy. However, this process produces residues in the form of fly ash and bottom ash (FABA), which contain harmful heavy metals such as Zn, Cu, Cr, Ba, and Ni. If not managed properly, these residues can pollute the environment because they are difficult to decompose and are potentially harmful to human health and ecosystems. This study aims to analyze the physical and chemical properties of FABA to determine its potential utilization. The results showed that fly ash has a finer particle size with a higher density than bottom ash which has coarser and larger particles. Based on ASTM C618 standard, FABA belongs to class C category, which shows SiO2 + Al2O3 + Fe2O3 > 50% content > 50%, and CaO content > 15%. FABA has the potential to be utilized in construction, where fly ash can be used as a partial substitute for cement, while bottom ash can replace sand. The utilization of FABA enables the production of environmentally friendly construction materials, such as rosters, bricks, and paving blocks, which are the result of recycling residues. Thus, the utilization of FABA also reduces the amount of residue generated by the incineration process and reduces dependence on natural raw materials, supporting the creation of a more sustainable construction industry. Keyword: fly ash, bottom ash, physical, chemical, recycling